ANALISIS HUBUNGAN PROPORSI PENGELUARAN DAN KONSUMSI PANGAN DENGAN KETAHANAN PANGAN RUMAH TANGGA PETANI PADI DI KABUPATEN KLATEN - HUSNUL AMALIYAH; SUGIHARTI MULYA HANDAYANI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2011)
The aim of this research are to analyse the proportion of food expendeture and consumption on the income of rice farmer household, to analyse energy and protein consumption of rice farmer household, and to analyse food security of rice farmer household in Klaten regency. This research used descriptive analysis method and executed survey technique. This research was done in Klaten Regency. Boto Village of Wonosari Subdistrict had chosen as research area purposively sampling. The data used in this research are primary and secondary data.